2020
DOI: 10.1186/s42483-020-00055-w
|View full text |Cite
|
Sign up to set email alerts
|

A Xanthomonas oryzae type III effector XopL causes cell death through mediating ferredoxin degradation in Nicotiana benthamiana

Abstract: Plant pathogenic bacteria engage in an ongoing struggle for survival. Gram negative phytopathogenic prokaryotes deploy type III secretion system to deliver effector proteins into plant cells to manipulate the host cellular environment. In many cases, the targets of these effector proteins are unknown. The bacterial blight pathogen, Xanthomonas oryzae pv. oryzae (Xoo), causes a devastating disease in rice and the Xoo-rice interaction is an example of the ongoing evolutionary battle between plants and pathogens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Xoo elicits a T3SS-dependent HR in Nb ( Li et al., 2012 ). Known Xoo factors that elicit HR in Nb include Hpa1, Ssb, XopL, XopP1, and XopY ( Li et al., 2013 ; Ma et al., 2020 ; Zou et al., 2006 ). In this study, the role of 17 Xoo TALE proteins in mediating the HR in Nb was systematically evaluated, and only AvrXa10 elicited a stable HR when transiently expressed in Nb ( Supplemental Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xoo elicits a T3SS-dependent HR in Nb ( Li et al., 2012 ). Known Xoo factors that elicit HR in Nb include Hpa1, Ssb, XopL, XopP1, and XopY ( Li et al., 2013 ; Ma et al., 2020 ; Zou et al., 2006 ). In this study, the role of 17 Xoo TALE proteins in mediating the HR in Nb was systematically evaluated, and only AvrXa10 elicited a stable HR when transiently expressed in Nb ( Supplemental Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the effectors XopQ from Xanthomonas and HopQ1 from Pseudomonas are recognized by Roq1 in the nonhosts Nicotiana benthamiana ( Nb ) and Nicotiana tabacum , resulting in ETI ( Wei et al., 2007 ; Schwartz et al., 2015 ; Schultink et al., 2017 ). Recently, our lab reported that the effector XopL from Xoo triggered an HR in Nb by interacting with ferredoxin ( Ma et al., 2020 ). Collectively, these studies indicate that nonhost plants possess a repository of R genes that could be deployed in plant disease resistance breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Xop, Xanthomonas outer protein; iTALE, interfering TALE; NLS, nuclear localization signals; AD, activation domain; TFB, transcription factor binding domain; TIP, TALE/iTALE interacting protein; NLR, nucleotide-binding leucine-rich repeat; CC, coiled-coil domain; BED, zinc-finger BED domain; NBS, nucleotide-binding site et al 2018). In addition, XopP interacts with the U-box domain of rice ubiquitin ligase PUB44 to inhibit ligase activity and suppress peptidoglycan-and chitin-induced immunity (Ishikawa et al 2014;Ichimaru et al 2022); XopY interacts with the rice receptor-like cytoplasmic kinase OsRLCK185 to inhibit rice immunity (Yamaguchi et al 2013); XopL catalyzes the ubiquitination of NbFd and induces defense-related response in plants (Ma et al 2020); XopZ, XopN, and XopV suppress the peptidoglycan-triggered PTI response (Long et al 2018); and XopN, XopQ, XopX, and XopZ suppress cell wall damageinduced immune responses in a functionally redundant manner (Sinha et al 2013). However, it is still a mystery what are the core Xops necessary for Xoo to cause BB in rice in the presence of a single major virulence TALE.…”
Section: The Interplay Between Tales and Non-tales Is Unknownmentioning
confidence: 99%
“…Silencing of OsPUB44 suppressed PGN- and chitin-triggered immunity (Ishikawa et al 2014 ). On the other hand, XopL itself exhibits E3 ubiquitin ligase activity and interacts with ferredoxin (NbFd), to target it for ubiquitination and ubiquitin-mediated degradation, thereby increasing reactive oxygen species (ROS) production (Ma et al 2020 ). XopI has also been shown to act as a F-box adapter and interacts with a thioredoxin protein, OsTrxh2, to strongly inhibit the host's OsNPR1-dependent resistance to Xoo (Ji et al 2020b ).…”
Section: Main Textmentioning
confidence: 99%